1997
DOI: 10.1046/j.1365-2958.1997.2281594.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MexE–MexF–OprN, a positively regulated multidrug efflux system of Pseudomonas aeruginosa

Abstract: Antibiotic-resistant mutants of Pseudomonas aeruginosa were generated using chloramphenicol and ciprofloxacin as selective agents. These mutants displayed a multidrug phenotype and overexpressed an outer membrane protein of 50 kDa, which was shown by Western blot analysis to correspond to OprN. A cosmid clone harbouring the oprN gene was isolated by partial complementation of a mutant deficient in OprM, the outer membrane component of the mexAB-oprM efflux operon. Antibiotic-accumulation studies indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
580
2
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(611 citation statements)
references
References 30 publications
(46 reference statements)
17
580
2
7
Order By: Relevance
“…This type of co-regulation has been described in nfxC type mutants of P. aeruginosa (43). These mutants overexpress the multidrug efflux pump MexEF-OprN (44), conferring resistance to quinolones, chloramphenicol, and trimethoprim, and are resistant to carbapenems due to decreased OprD expression (44,45). Interestingly this resistance phenotype can be obtained in the susceptible wild type PT5 upon plasmid-mediated overexpression of MexT, the transcriptional activator of the MexEF-OprN efflux pump (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of co-regulation has been described in nfxC type mutants of P. aeruginosa (43). These mutants overexpress the multidrug efflux pump MexEF-OprN (44), conferring resistance to quinolones, chloramphenicol, and trimethoprim, and are resistant to carbapenems due to decreased OprD expression (44,45). Interestingly this resistance phenotype can be obtained in the susceptible wild type PT5 upon plasmid-mediated overexpression of MexT, the transcriptional activator of the MexEF-OprN efflux pump (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…These mutants overexpress the multidrug efflux pump MexEF-OprN (44), conferring resistance to quinolones, chloramphenicol, and trimethoprim, and are resistant to carbapenems due to decreased OprD expression (44,45). Interestingly this resistance phenotype can be obtained in the susceptible wild type PT5 upon plasmid-mediated overexpression of MexT, the transcriptional activator of the MexEF-OprN efflux pump (46,47). MexT overexpression was shown to decrease both transcriptional (46,47) and posttranscriptional expression of oprD (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains and plasmids used in this work are listed in Table 1. The P. aeruginosa nfxC-type strain PT644 is a mexB::⍀Hg derivative obtained by transduction of the Hg cassette from the mexB::⍀Hg strain PAM1275 (kindly provided by O. Lomovskaya) into strain PT149 (nfxC) (formerly called PAO-7H) (12). Disruption of the mexF gene in strain PT644 resulted in the ⌬mexF derivative PT644⌬F (see below).…”
Section: Methodsmentioning
confidence: 99%
“…In several clinically isolated mutants of P. aeruginosa, higher expression of RND-type efflux pumps was observed (Hirai et al, 1987;Rella & Haas, 1982;Wolter et al, 2004). Of the 11 RND efflux pumps identified in this organism, 10 pumps, MexAB-OprM (Poole et al, 1993), MexCD-OprJ (Poole et al, 1996), MexEF-OprN (Kohler et al, 1997), MexGHI-OpmD (Aendekerk et al, 2002;Sekiya et al, 2003), MexJK (Chuanchuen et al, 2002), MexMN (Mima et al, 2005), MexPQ-OpmE (Mima et al, 2005), MexVW (Li et al, 2003), MexXY (Mine et al, 1999;Westbrock-Wadman et al, 1999) and TriABCOpmH (Mima et al, 2007), have been experimentally confirmed, and their properties have been reported. The RND-type efflux pump usually consists of three components to fulfil the function properly and includes an innermembrane component (RND component), a periplasmic component (MFP component), and an outer-membrane component (OMP component) (Touze et al, 2004), and the three-dimensional structures of MexA, MexB and OprM have been reported (Akama et al, 2004a, b;Higgins et al, 2004;Sennhauser et al, 2009).…”
Section: Introductionmentioning
confidence: 99%